A pilot short-term study of feasibility, acceptability and preliminary efficacy of 3-stage 8-session 4-week group therapy-based narrative intervention in 17 improved hospitalized female schizophrenia patients in southern China - Qian Zhou; Yuhua Wei; Zaifei Huang; Yue Zhao; Sujiao Qin; Xuewei Wei; Lianou Wei; Da Huang; Mingkang Qin; Lingjun Zeng; Fengqiong Qin; Yuting Huo (Frontiers in Public Health)
Self-stigma has been consistently cited as a major obstacle to recovery-related outcomes among patients with schizophrenia. To examine the feasibility, acceptability, and preliminary efficacy of the group-based narrative intervention for improving self-stigma, self-esteem and psychological capital in hospitalized patients with schizophrenia, a case-series study was conducted from March to May 2023 in a closed psychiatric ward of a specialized hospital in mainland China. Feasibility was assessed by examining rates of recruitment, retention, and protocol adherence. Acceptability was assessed through the therapist’s and patients’ feedback about the intervention. Changes in the levels of self-stigma, self-esteem, and psychological capital perceived by patients were measured before and after 4 weeks of intervention. Rates of enrolment (85%) and completion of intervention sessions and study procedures (100%) were excellent, demonstrating high rates of feasibility among these patients in the local setting. The feedback from participants and the therapist about satisfaction, helpfulness, and difficulty of the intervention was largely positive, demonstrating high rates of acceptability. And the results indicated significant improvements in patients’ self-reported self-stigma, self-esteem, and psychological capital (change in T = 3.872, p = 0.001; T = −6.308, p < 0.001; T = −2.895, p = 0.011, respectively). The study provided a structured intervention program for clinical care to reduce self-stigma and promote positive recovery outcomes for inpatients with schizophrenia.